Potential of Photobiomodulation to Induce Differentiation of Adipose- Derived Mesenchymal Stem Cells into Neural Cells - Van Rensburg, Madeleen J.; Crous, Anine; Abrahamse, Heidi (Current Stem Cell Research & Therapy, 2021)
Background: Given the minimal capacity and sometimes the failure of the mammalian nervous system to regenerate and repair itself after damage, strategies are required to help enhance this regenerative process. Adipose-derived Mesenchymal Stem Cells (ADMSCs) are likely candidates to assist in the recovery process due to their ability to differentiate into neural cells. Successful implementation of this intervention in a clinical setting would increase the rate of recovery following traumatic brain injury. Review: Various strategies have been attempted to differentiate ADMSCs into neural cells for clinical use. Such methods have not been entirely successful in the development of functioning specialized cells for subsequent practical use. Therefore, the implementations of this differentiation technique in the clinical trial have not been effective. In this article, the potential of differentiating ADMSCs into neural cells and the various methods employed, including biological induction, chemical induction and photobiomodulation (PBM) will be discussed, where the combined use of transducers and PBM for neural differentiation of ADMSCs is also deliberated. Conclusion: PBM shows promise as an avenue for effective ADMSCs differentiation into neural cells and their proliferation. Applying PBM with optimized biological factors and chemical inducers may prove to be an effective tool for clinical application.
Keywords: neural regeneration